2004
DOI: 10.2337/diacare.27.4.895
|View full text |Cite
|
Sign up to set email alerts
|

Cost Analysis of Human Islet Transplantation for the Treatment of Type 1 Diabetes in the Swiss-French Consortium GRAGIL

Abstract: OBJECTIVE -To evaluate the cost of islet transplantation in type 1 diabetic patients with a functional renal graft in a multicenter network.RESEARCH DESIGN AND METHODS -The study involved nine diabetic patients transplanted in the Swiss-French Groupe Rhô ne-Alpes, Rhin et Geneve pour la transplantation d'Ilots Langerhans (GRAGIL) consortium between March 1999 and June 2000. The direct medical costs were estimated from Social Security's perspective from the inclusion of the patient to 1 year after transplantati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 25 publications
(17 reference statements)
2
34
0
Order By: Relevance
“…In 2004, a French study evaluated the cost of islet transplantation from the time of organ removal until the transplant itself and its follow-up. The study found that islet isolation was the most expensive phase of the process, accounting for 30% of total transplant costs (36). A similar situation has been reported in Brazil, where the reliance on imported isolation reagents may lead costs to rise even further (61).…”
Section: Islet Transplantation and The Current Status Of This Procedusupporting
confidence: 62%
See 1 more Smart Citation
“…In 2004, a French study evaluated the cost of islet transplantation from the time of organ removal until the transplant itself and its follow-up. The study found that islet isolation was the most expensive phase of the process, accounting for 30% of total transplant costs (36). A similar situation has been reported in Brazil, where the reliance on imported isolation reagents may lead costs to rise even further (61).…”
Section: Islet Transplantation and The Current Status Of This Procedusupporting
confidence: 62%
“…However, the clinical applicability of islet transplantation in many health centers is limited by the complexity of islet isolation processes, the high cost (34,36) and the scarcity of donor organs (37). Since each transplant patient generally requires islets isolated from two to three donors in order to improve rates of insulin independence (37), there is a significant interest in developing methods for isolating the greatest number of viable islets from the pancreas of each donor.…”
Section: Islet Transplantation and The Current Status Of This Procedumentioning
confidence: 99%
“…The mean length of hospitalization was 5.8 days/islet infusion/patient. Our group previously published a 1-year cost analysis of islet transplantation and described a mean hospitalization length of 15.6 days/patient over 1 year with total costs slightly higher than the costs of whole-organ pancreas transplantation (38). During the entire 5 years of follow-up, mean hospitalization duration, including all hospitalization stays for each islet infusion, and eventually for the occurrence of adverse events, fell to 7.05 days/patient/year.…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies assessed only pancreata preserved for a relatively short period of CIT [12,13]. Currently, efforts are ongoing to centralize clinical islet isolation in highly experienced units to maximize resources and reduce costs [14,15]. On the other hand, this may result in prolonged transportation, thus increasing CIT.…”
Section: Introductionmentioning
confidence: 99%